Business and peace-building the role of natural resources companies - Bond, Carol Janson (Routledge, Taylor and Francis Group, 2019)
"In a world struggling to adapt to seismic social and environmental changes, the time is now for businesses to prioritise creating local conditions of peace. This book builds on original research foregrounding 'peace' as a core business outcome for natural resources industries. Especially in non-warlike situations where natural resources industries have exacerbated or caused conflict, foregrounding peace as a core business outcome can bring substantial benefits. Peace is a concept external and internal stakeholders understand. Consequently, research shows that when natural resources sector CSR professionals start reframing their day-to-day decisions in terms of peace outcomes, they are more likely to create efficient and cost-effective solutions to environmental, social and economic business challenges. This book provides both theory and practical suggestions for how to reframe day-to-day CSR activities of natural resources companies as peace-focused, business decisions. Especially in the remote and rural regions of the world where natural resources industries have the greatest impact, businesses can lead the way in contributing to conditions of peace while bringing much needed resources to market"--
Includes index. - Includes bibliographical references and index. - Description based on print version record
Keywords: Social responsibility of business; Business ethics; Peace-building; Natural resources -- Management; Entreprises; Responsabilité sociale; Morale des affaires; Consolidation de la paix; Ressources naturelles; Gestion; Natural resources; Management